Comparison of Risk of Target Organ Damage in Different Phenotypes of Arterial Stiffness and Central Aortic Blood Pressure - Bai, Yaya; Wang, Qian; Cheng, Di; Hu, Yueliang; Chao, Huijuan; Avolio, Alberto; Tang, Biwen; Zuo, Junli (Frontiers in Cardiovascular Medicine, 2022)
Objectives The aim of this study was to explore the risk of target organ damage (TOD) in different groups based on carotid-femoral pulse wave velocity (cfPWV) and central aortic blood pressure (CBP) in different populations. Methods The study cohort was divided into four groups according to the status of cfPWV and CBP [Group (cfPWV/CBP): high cfPWV and high CBP; Group (cfPWV): high cfPWV and normal CBP; Group (CBP): normal cfPWV and high CBP; Group (control): normal cfPWV and normal CBP]. TOD was determined by the assessment of carotid intima-media thickness (CIMT) abnormality, chronic kidney disease (CKD), microalbuminuria, and left ventricular hypertrophy (LVH). Results A total of 1,280 patients (mean age 53.14 ± 12.76 years, 64.1% male patients) were recruited in this study. Regarding Group (control) as reference, LVH was significantly higher in Group (cfPWV) and Group (CBP) [OR 2.406, 95% CI (1.301–4.452), P < 0.05; OR 2.007, 95% CI (1.335–3.017), P < 0.05]; microalbuminuria was significantly higher in Group (cfPWV/CBP) and Group (CBP) [OR 3.219, 95% CI (1.630–6.359), P < 0.05; OR 3.156, 95% CI (1.961–5.079), P < 0.05]. With age stratified by 60 years, the risk of CKD was significantly higher in Group (cfPWV/CBP) [OR 4.019, 95% CI (1.439–11.229), P < 0.05]. Conclusion Different phenotypes based on the status of cfPWV and CBP were associated with different TOD. Individuals with both cfPWV and CBP elevated have a higher risk of microalbuminuria.